TANTANGAN SISWA SD DALAM MEMAHAMI KALIMAT PENJUMLAHAN DAN STRATEGI GURU: KAJIAN LITERATUR - Amir Mahmud Hasibuan; Noven Christoper Butarbutar; Niko Alriadi Sinaga (Universitas Negeri Medan, 2025)
Understanding mathematical sentences is a crucial factor in students’ success in learning whole number addition in elementary school. However, many students still struggle to interpret mathematical language, especially in word problems. These difficulties include interpreting key terms, identifying essential information, and translating verbal statements into mathematical models. Internal factors such as low motivation, math anxiety, and limited language skills, along with external factors like monotonous teaching methods, further contribute to these challenges. To address this, teachers need to implement effective strategies such as the use of concrete media, contextual approaches, guided reading of problems, and remedial programs. Overall, teachers play an essential role in designing interactive and meaningful learning to improve students’ numeracy literacy.